Epidemiology and burden of pediatric burns in underdeveloped minority areas in Guangxi, China from 2014 to 2020: a retrospective study - Lin, Ziren; Al-Saidi, Nahlah Abduljaleel Yahya; Lin, Jiamei; Wu, Yongfang; Lan, Liuting; Huang, Cheng; Liang, Feiteng; Huang, Zhiqun (Frontiers in Public Health, 2025)
BackgroundBurns are a significant cause of accidental injuries in children worldwide. This study investigated the epidemiology and burden of pediatric burns to identify the associated factors with these injuries and to formulate prevention strategies in underdeveloped minority areas in Guangxi, China.MethodsA retrospective study was conducted on 660 pediatric burns admitted to two tertiary hospitals in Baise, Guangxi. Demographic data, burn characteristics, clinical factors, and burden information were analyzed. Multiple linear regression was performed to identify the associated factors associated with the length of hospital stay (LOHS) and costs.Results660 pediatric burn cases were recorded from January 2014 to December2020. The median age of pediatric burn patients was 2 years. Winter is the peak period of pediatric burns. Scalding was the most frequent cause followed by flame burns. The median total body surface area (TBSA) affected being 6%. The median length of hospital stay (LOHS) was 9 days. The median cost was 7,558 CNY. The major associated factors for LOHS were the response rate [standardized beta coefficient (SBC) = 0.391], TBSA (SBC = 0.357), operations (SBC = 0.350). The major associated factors for cost were LOHS (SBC = 0.468), TBSA (SBC = 0.306), operations (SBC = 0.215), response rate (SBC = 0.120) and region (SBC = 0.081). The p value of all associated factors were p < 0.05.ConclusionScalds and flame burns are key targets for prevention among children under 3 years in underdeveloped minority areas of Guangxi, China. Winter is identified as the peak season for pediatric burns. The burden of pediatric burns is associated with multiple associated factors; these findings provide a foundation for assessing the epidemiology and burden of pediatric burns in this areas. Given the central role of caregivers in daily child supervision, addressing their knowledge, caregiving practices, and environmental awareness—alongside consideration of the broader contextual factors—can help foster a safer and more sustainable caregiving environment for children.